Utilization of corn-dried distiller grains with solubles from China in broiler diets - Tang, Siew Ching (2011)
Corn-dried distiller grains with solubles (CDGS) is a co-product of ethanol production which contains much of the original nutritional value of the corn. There is a considerable information on the use of US source of CDGS in poultry diets but not those from China. Corn grown from different geographic locations can affect the nutrient content of CDGS. A series of experiments were conducted to examine the effect of feeding CDGS and enzyme complex (AllzymeTM SSF) supplementation on broiler performance. The first experiment was conducted to determine the nutrient composition of 12 different sources among the US (5 sources) and Chinese (CN 7 sources) CDGS, followed by two studies for nitrogen corrected true metabolizable energy (TMEn) and true ileal amino acids digestibility (TIAAD) values of CN1 CDGS, based on total excreta and ileal digesta collection, respectively. The findings showed that the nutrient contents of CDGS samples were about two to three times more concentrated than those of corn grain except for gross energy and amino acids concentrations whose values were almost similar to those of corn grain. However, the chemical properties of CDGS from various sources differed considerably and greater variability in most nutrients was noted among the Chinese source of CDGS when compared to US samples that was more consistent. The TMEn of the determined CN1 CDGS for 5-week-old broiler chicken was 2924 cal/kg, and showed high TIAAD (83 - 98%) for all amino acids except for threonine and arginine (60% and 66%, respectively). In conclusion, different sources of CDGS contain a greater variability in nutrient content, but CDGS is a good nutrient source and can be used as an alternative feed ingredient in broiler diets. In experiment II, a completely randomized design with 5 treatments (6 replicates per treatment) was utilized to evaluate the effects of feeding CDGS on growth performance , carcass yield and meat fatty acid composition of chickens. A total of 300 male broilers (Cobb 500) were fed with different levels of CN1 CDGS (0% -control, 5%, 10%, 15%, and 20%) in starter (age 0 to 21 d) and grower (age 21 to 42 d) diets. All diets were formulated isocaloric and isonitrogenous which met or exceeded the NRC requirements. Birds fed 5% CDGS had better (P < 0.05) feed conversion ratio than those fed 10%, 15% or 20%, but were not different (P > 0.05)from the control over 42 d. There were no differences (P > 0.05) in overall weight gain, feed intake, dressing percentages and carcass part yields (% of carcass weight)among treatments over a period of 42 d. There were increasing (P < 0.05)percentages of linoleic acid (18:2 n-6) and polyunsaturated to saturated fatty acid ratios (P < 0.05) in both the breast and thigh meats with increasing levels of dietary CDGS. In conclusion, incorporating 5% of CDGS in the broiler diet did not affect (P > 0.05), while levels higher than that were detrimental to growth performance and carcass yield. However, increasing the dietary CDGS level increased (P < 0.05) the percentage of linoleic acid and polyunsaturated to saturated fatty acid ratio in chicken meat. In experiment III, a 2 x 3 factorial experiment arranged in a randomized complete design with 6 treatments (6 replicates per treatment) was conducted to evaluate the effects of feeding CDGS with enzyme supplementation on growth performance and nutrient availability in broiler chickens. A total of 360 broiler chicks (Cobb 500) in equal number of males and females were fed with corn-soy based diets with or without (control) 15% of CDGS and 3 levels of a commercial enzyme (Allzyme SSF at 0, 200 and 400 mg/kg) in starter (age 0 to 21 d) and grower (age 21 to 42 d) diets. All diets were formulated isocaloric and isonitrogenous which met or exceeded the NRC requirements. Feeding chicks with 15% corn CDGS significantly (P < 0.05)depressed body weight, increased feed intake, increased feed conversion ratio and lower energy value of diet when compared to those chicks fed control diet. However,addition of 15% CDGS significantly (P < 0.05) increased phosphorus content of tibia bone. In general, there were no significant differences in all the productive parameters measured between birds supplemented with different levels of commercial enzyme (0, 200, and 400 mg/kg) into broiler diets over 42 d. In the present study, there was a lack of interaction between the two factors (diet x enzyme) for the performance parameters, either over the starter (day 0 to 21) or grower (day 21 to 42) period. Irrespective of diet type, higher dose of commercial enzyme (400 mg/kg) caused a reduction in feed consumption at weeks 1 and 4, and depressed body weight in young chicks (day 0-21). In conclusion, incorporating 15% of CDGS in broiler diet significantly reduced their growth performance. In addition, commercial enzyme supplementation had negligible effect on the overall growth performance and nutrient availability including nitrogen corrected apparent metabolizable energy (AMEn), phosphorus and calcium availability in broilers fed 15% CDGS.